Social entrepreneurship intention among undergraduate students in Universiti Utara Malaysia - Nurhawanis, Muhamad Mukhatarruddin (2023)
The main objective of this study is to investigate social entrepreneurship intention among undergraduate students in Universiti Utara Malaysia (UUM). This research also investigates the relationship between attitude, influence of norm, perception control and individuals' sustainability orientation towards social entrepreneurship intention. The inconsistency of findings in past literature between the relationship social entrepreneurship intention has prompted researchers to explain the inconsistency. The survey questionnaire was distributed using an online questionnaire to undergraduate students of Universiti Utara Malaysia. A total of 321 questionnaires were used for analysis. The direct relationship was analyzed using the PLS-SEM method. The results show that attitude, influence norm and perception control have a significant relationship with social entrepreneurship intention while individuals' sustainability orientation is found to be insignificant. Finally, management implications, study limitations, and future research recommendations are discussed.